2021
DOI: 10.3390/jof7040292
|View full text |Cite
|
Sign up to set email alerts
|

Triazole-Resistance in Environmental Aspergillus fumigatus in Latin American and African Countries

Abstract: Triazole-resistance has been reported increasingly in Aspergillus fumigatus. An international expert team proposed to avoid triazole monotherapy for the initial treatment of invasive aspergillosis in regions with >10% environmental-resistance, but this prevalence is largely unknown for most American and African countries. Here, we screened 584 environmental samples (soil) from urban and rural locations in Mexico, Paraguay, and Peru in Latin America and Benin and Nigeria in Africa for triazole-resistant A. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
(55 reference statements)
2
24
0
3
Order By: Relevance
“…Coincidentally, the first resistant clinical isolate carrying TR 34 /L98H was reported infecting a patient in 1998 [ 14 , 30 ], just a few years after triazole fungicides had been introduced into the Netherlands [ 30 ], which suggests that this mutant could had emerged after azole fungicide contact in the field. Eventually, the TR 34 /L98H mutation was identified in many other European countries, and also in Asia, North and South America, Australia, and Africa [ 25 , 43 ].…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…Coincidentally, the first resistant clinical isolate carrying TR 34 /L98H was reported infecting a patient in 1998 [ 14 , 30 ], just a few years after triazole fungicides had been introduced into the Netherlands [ 30 ], which suggests that this mutant could had emerged after azole fungicide contact in the field. Eventually, the TR 34 /L98H mutation was identified in many other European countries, and also in Asia, North and South America, Australia, and Africa [ 25 , 43 ].…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…High frequencies of ARAf have been detected in urban planted areas, for example, in the air above parks, in botanical gardens and other flowerbed soils, and flowerpot soil from urban locations (Supplementary Table S1). With some exceptions (e.g., [83]), these detection frequencies have also exceeded those for agricultural soils [35,60,84]. Given that DMIs are not applied as intensively in urban settings as in agronomic settings, it is conceivable that plant waste (presumably in the form of compost) from agricultural produce consumed in urban centres creates a local context for the amplification of ARAf, especially if it carries DMI residues (as suggested by Duong et al [40]), or that previously-composted materials transfer ARAf to urban settings.…”
Section: The Role Of Plant Waste In the Amplification And Spread Of Arafmentioning
confidence: 99%
“…Sewell et al [35] found the highest incidence of ARAf, with the greatest genotypic diversity, in soils from the urban environment of central London, rather than in samples from farmland, woodland, and pasture. A study of soil samples taken in five countries in South America and Africa [84] showed that ARAf was more prevalent in samples from urban sites than in those from agricultural land: mutants including TR 34 /L98H and TR 46 /Y121F/T289A were found in DMI-contaminated agricultural soils (in Peru), but also in urban flower bed soils lacking DMI residues (in Mexico and Paraguay). Tangwattanachuleeporn et al [85] did not recover ARAf isolates from soil sampled in metropolitan areas of Thailand, but they found resistant isolates in only ca.…”
Section: Comparison Of Urban and Agronomic Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 In addition, azole-resistant and azole-susceptible A. fumigatus strains harboring non-synonymous mutations F46Y, M172V, N248T, D255E, and E427K in the cyp51A gene have been isolated repeatedly from environmental and clinical samples throughout the world. [54][55][56][57] These amino acid substitutions have been shown to be located in the peripheral regions of the CYP51A protein, without interfering in the access channels for the binding of the azole compounds. 58 Therefore, the five mutations are regarded as polymorphisms of the cyp51A gene.…”
Section: Azole Resistance Of Aspergillus Fumigatus In the Environmentmentioning
confidence: 99%